FORGET ME NOT - Reawakening Caroli Church, a building between times - Sjöberg,Sophie (2025)
In the centre of Malmö, Caroli Church stands in quiet suspension—its doors closed, its future uncertain. Neither abandoned nor alive, it occupies a space between preservation and possibility. In a society where churches are increasingly disconnected from their original function, the question lingers: what becomes of the sacred when it no longer serves the ritual? And who, ultimately, decides what these spaces might become? In Malmö—a city shaped by migration, movement, and cultural plurality—Caroli Church stands as both a remnant and a resource. This project is not only an architectural investigation, but also a poetic, material, and political reflection on how we engage with our built heritage. Caroli Church is reimagined not as a new function dressed in old stone, but as a woven fabric—layers of history, material, and memory intersecting with contemporary needs for gathering, movement, and listening. A music library, yes—but also a place where voices, footsteps, tones and silences resonate in shared space. In a place once defined by collective silence and song, music offers another form of resonance. The method begins in what already exists—its stone, its metals, its patina—allowing new elements to emerge not to overpower or diminish, but to mirror, to shift, to respond. The mezzanine, the furnishings, the inserted layers speak the language of the church—limestone, zinc-coated steel, timber—but with a new syntax. The historical foundation, preserved since the 17th century, now carries a contemporary narrative as well. In parallel, a series of comparative studies unfolds: churches transformed into book sanctuaries, civic living rooms, exclusive clubs. These precedents—from the Netherlands, Denmark, and Sweden—have not served as templates, but as sources of inspiration in a conversation on architecture’s potential to both uphold and disrupt conventions. Rather than proposing a definitive solution, this project seeks to articulate a form of resistance: against regulatory paralysis, against architectural timidity, against the notion that respect must always mean restraint. For at times, it is precisely through transformation that something is allowed to remain.
Keywords: Keywords: Architecture; Caroli Church; Malmö; adaptive reuse; cultural heritage; ecclesiastical buildings; transformation; living heritage; sustainable development; music and culture